Moths and butterflies (Insecta: Lepidoptera) of the Russian Arctic islands in the Barents Sea - Kullberg J.; Filippov B.; Spitsyn V.; Zubrij N.; Kozlov M. (Springer Verlag, 2022)
Faunistic data are scarce for the Lepidoptera from the Arctic islands of European Russia. New sampling and revision of the earlier findings have revealed the occurrence of 60 species of moths and butterflies on Kolguev, Vaygach and Dolgij Islands and on the Novaya Zemlya archipelago. The faunas of Kolguev and Dolgij Islands (19 and 18 species, respectively) include typical moths of the northern taiga (Aethes deutschiana, Syricoris lacunana and Xanthorhoe designata), and the low numbers of species discovered on these islands have resulted primarily from low collecting efforts. By contrast, the fauna of Vaygach Island (22 species) is relatively well known and includes several high Arctic species, such as Xestia aequaeva, X. liquidaria and X. lyngei. Nevertheless, Vaygach Island is depauperated even relative to the fauna of Amderma (29 species), which is located on the continent next to the Vaygach Island. The fauna of Novaya Zemlya totals 30 species, but only eight of these were collected from the Northern Island, mostly near Matochkin Shar strait. Noteworthy is the record of Plutella polaris from Novaya Zemlya: this species was recently re-discovered in Svalbard, where the type series was collected in 1873. Udea itysalis, described from North America, is reported here for the first time from Europe. The fauna of the Russian Arctic islands in the Barents Sea is dominated by holarctic species, many of which are confined to tundra habitats. We estimate that some 40–60 moth species remain to be found in this region.